Development and evaluation of a new instrument that measures motivation towards academic achievement (IMLA) in higher education - Lagos San Martín, Nelly Gromiria; Roa Venegas, José María; Palma Luengo, Maritza Roxana; López López, Carmen Verónica; Fernández Prados, Carmen (Technium Social Sciences Journal, 2024)
Academic motivation in teaching and learning processes, both in general and in particular in higher education, has been of great interest in educational research, since it is the basis of academic success. In this work, the model "Expectations-Value of achievement motivation" has been considered, which uses a socio-cognitive perspective to design an inventory that allows measuring the motivation for academic achievement in higher education. With this objective, the Motivational Inventory of Academic Achievement (IMLA) is created, supported by a rigorous methodological process in order to make this instrument reliable and valid. The psychometric properties of the IMLA were determined from the analysis of content validity, reliability and construct in a sample of 464 higher education students from a Chilean and a Spanish university. The results indicate that the IMLA has 9 factors that explain 64.11% of the total variance and a Cronbach’s alpha of .913, a rating considered high according to the requirements of a measurement instrument. In this way, this study contributes with the creation of a tool that integrates important motivational aspects focused on internal cognitive beliefs, based on expectations and the value of the task, as well as incorporating the assessment of the environment, for which reason it is estimated. that the IMLA is an instrument with a high potential for the educational and scientific field.